CHOLINE PREPARATIONS IN THE TREATMENT OF ASTHENIC STATES: MODERNITY AND PERSPECTIVES (A LITERATURE REVIEW WITH A CLINICAL CASE PRESENTATION) - Kamila Sh. Magomedova; Yuriy V. Bykov; Roman A. Bekker (Siberian Journal of Life Sciences and Agriculture, 2023)
Purpose. To provide the reader with a detailed description of the biochemical and physiological effects of choline, which make it an indispensable component of our daily food. Then to thoroughly review all the relevant clinical data on the use of choline preparations for the treatment of asthenic and astheno-depressive conditions and cognitive impairments. Then, to present the reader with a clinical case from our own practice, illustrating the effectiveness of the use of choline alfoscerate as part of the combination therapy of a mild form of post-COVID astheno-depressive syndrome in a 19-year-old man who have refused to take antidepressants, as well as any other psychotropic drugs, but instead wanted some form of pharmacotherapy based exclusively on «natural components».